2022
DOI: 10.1038/s41598-022-13063-x
|View full text |Cite
|
Sign up to set email alerts
|

IL-7/IL7R axis dysfunction in adults with severe community-acquired pneumonia (CAP): a cross-sectional study

Abstract: Community-acquired pneumonia (CAP) is a worldwide leading cause of death. Recognized risk factors in some severe cases have not been identified. Lymphocytopenia has been frequently described in CAP. Since IL-7, membrane-bound receptor (IL7Rα;CD127) and soluble IL7Rα (sIL7R) are critical in lymphocytes homeostasis, in this work we aimed to evaluate the involvement of the IL-7/IL7Rα axis in the severity of adult CAP, since it has not been explored. The IL7Rα SNPs rs6897932, rs987106, and rs3194051 SNPs in IL7α w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…For example, a study showed that targeting ICOS molecules on T cells alleviates immune-mediated influenza pneumonia ( 19 ). Additionally, research has shown that PD-1 and ICOS counter-regulates the development of tissue-resident regulatory T cells and the production of interleukin (IL)-10 in influenza ( 20 ), and sIL7R levels are significantly associated with SNPs in the IL7R gene in adult CAP, and increased plasma sIL7R may help identify the adult CAP patients at risk of death ( 21 ). Further, research has shown that Bruton’s tyrosine kinase/ITK dual inhibitors modulate immunopathology and lymphopenia in coronavirus disease 2019 (COVID-19) treatment ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study showed that targeting ICOS molecules on T cells alleviates immune-mediated influenza pneumonia ( 19 ). Additionally, research has shown that PD-1 and ICOS counter-regulates the development of tissue-resident regulatory T cells and the production of interleukin (IL)-10 in influenza ( 20 ), and sIL7R levels are significantly associated with SNPs in the IL7R gene in adult CAP, and increased plasma sIL7R may help identify the adult CAP patients at risk of death ( 21 ). Further, research has shown that Bruton’s tyrosine kinase/ITK dual inhibitors modulate immunopathology and lymphopenia in coronavirus disease 2019 (COVID-19) treatment ( 22 ).…”
Section: Discussionmentioning
confidence: 99%